An Overview On Ottoman Manuscript Collection in the Sayyid Muhammad Naquib Al-Attas Library - Özay, Mehmet (Studia Islamika, 2023)
This paper endeavors to give a quick view of the Ottoman manuscript (Osmanlı elyazmaları) collection at Sayyid Muhammad Naquib Al-Attas Library (SMNAL) of the International Institute of Islamic Thought and Civilization (ISTAC) International Islamic University Malaysia (IIUM) by reviewing a published catalog. The Ottoman manuscripts, which mean texts written in the Ottoman Turkish language, were collected during the first part of the 1990s, inventoried, and cataloged during the early period of ISTAC. The collection possesses two hundred manuscripts on diverse subjects. This makes the SMNAL the most pertinent library in Southeast Asia, a place hoard of Ottoman Turkish manuscripts. This initiation of acquiring a certain number of Ottoman manuscripts by Sayyid Muhammad Naquib al-Attas which seems to have been purchased in the late decades of the twentieth century is no doubt an opening towards the path to the study of the Ottoman civilizational and intellectual eco-system among the Malay scholars and students of the Ottoman studies (Turcologists).